Diagnóstico de la gestión de la innovación del sector turístico del cantón Portoviejo en el contexto del covid-19 - Loor Quijije, Gabriela Valentina (2022)
The purpose of this study was to diagnose the management of innovation to strengthen the tourism sector in Portoviejo canton in the context of COVID-19. Thisresearch is of an exploratory descriptive nature. In the first phase, the canton was characterized in relation to the current technological prospective, in the second phase the criteria for the analysis were integrated according to the sectors, areas, dimensions and stages that must be measured. In the third phase, a procedure was outlined for the analysis of innovation in a tourist destination based on the criteria extracted from the bibliographic review, from which indicators validated by experts were established that allowed knowing the state of the invention under the criterion of the demand. It was observed that thePortoviejo canton isin a technological development phase but haslimitations in innovative tourism activity. 25 indicators were defined according to the criteria of the experts that allow the measurement to be carried out in three stages (before, during and after the visit). The survey showed that the demand considers that Portoviejo has innovative infrastructure with clearly differentiated tourist sites in relation to nearby destinations, however, 42.1% of the sample indicated having limited knowledge on the subject of study. Finally, the research shows that Portoviejo has the potential to become a smart tourist destination but requires proper management, driven by various sectors.